Tobacco industry strategies to undermine the 8th World Conference on Tobacco or Health. (1st June 2003) - Muggli, M E; Hurt, R D
Abstract : Objective: To demonstrate that Philip Morris and British American Tobacco Company attempted to initiate a wide ranging campaign to undermine the success of the 8th World Conference on Tobacco or Health held in Buenos Aires, Argentina, in 1992. Data sources: Publicly available tobacco industry documents housed in Minneapolis, Minnesota, USA; Guilford, UK; on-line document websites; and telephone interviews with informed parties. Study selection: Those documents determined to be relevant to the companies' campaigns against the 8th World Conference on Tobacco or Health. Data extraction: Revision of chapter VIII of the July 2000 WHO report by a committee of experts, entitled: Tobacco company strategies to undermine tobacco control activities at the World Health Organization: report of the committee of experts on tobacco industry documents . Data synthesis: Internal documents describe proposed media and science orientated campaigns developed by BAT, Philip Morris, and their consultants to divert attention away from the conference. Results and conclusion: This work shows that the tobacco industry has the resources and vested interest to combat perceived threats in its regional operating markets, in this case its Latin American market. It is important for the worldwide public heath community to become aware of the numerous ways in which the tobacco industry and its front groups can work against international tobacco control meetings, even including the manipulation of or working with other public health groups to oppose tobacco control efforts. Future world conference planners and participants should be aware that the tobacco industry is likely to continue to employ such methodology. There is no reason to think that the industry is paying less attention to such conferences in the present or future. Rather, it is likely the industry will adopt and expand strategies that were successful while abandoning those that were not effective. Required disclosure of financial support by all participants at all tobacco scientific conferences is recommended. For the tobacco control community, we also recommend careful coalition building and networking with other public health groups on the ways tobacco is implicated in other public health issues.